Communicating Politics and National Identity: The Case of Mozambique - Gonçalves, Gisela (2020)
This chapter questions if and how political communication is being used as a tool to build national identity in Mozambique, a country deeply divided in socio-economic, cultural and political terms. Focusing on Armando Guebuza’s Open and Inclusive Presidencies, it aims to present a picture of Mozambique regarding the following entwined issues: (1) the political system, including the electoral system and political participation trends; (2) the media system, including the media landscape and media ownership; and (3) the government communication structure and strategies.